Hepatoprotective effect of leaf extracts from Citrus hystrix and C. maxima against paracetamol induced liver injury in rats - Arumugam Abirami; Gunasekaran Nagarani; Perumal Siddhuraju (Food Science and Human Wellness)
The present investigation is aimed to evaluate the hepatoprotective effects of Citrus hystrix and Citrus maxima (Red and White variety) methanolic leaf extracts on paracetamol induced toxicity. Leaf extracts were given in the dose of 200 mg/kg body weight for 7 days and toxicity was induced by paracetamol (2 g/kg) on day 5. Silymarin (100 mg/kg body weight) was used as reference standard. On the 7th day animals were sacrificed and liver function markers (ALT, AST, ALP), total bilirubin and total protein in blood serums and hepatic antioxidants (SOD, CAT, GSH and GPx) in liver homogenate were estimated. The leaf extracts restored the liver function markers and hepatic antioxidants to the normal level than elevated levels noticed on paracetamol control at P < 0.001. Reversal of hepatoarchitecture has also been registered. The present study shows that C. hystrix and C. maxima leaf extracts possess hepatoprotective action against paracetamol induced hepatotoxicity.